PERANAN THE UNITED NATIONS CHILDREN’S FUND (UNICEF) DALAM PENANGANAN EKSPLOITASI SEKSUAL KOMERSIAL ANAK (ESKA) DI DUNIA - Maharany Fitri; Chairul Bariah; Arif Arif (Journal of USU International Law, 2016)
ABSTRACT Maharany Fitri* Dr. Chairul Bariah, S.H., M.Hum.** Arif, S.H., M.Hum.*** Child Commercial Sexual Exploitation is a basic violation to the rights of children. These violations consist of sexual abuse from adults and rewards in a form of money or object for the child, third parties, or other parties. Child Commercial Sexual Exploitation can take form in Child Prostitution, Early-age Marriage, Child Pornography, or even Child Sex Tourism. In Principle, International law already legislate a law about Child Commercial Sexual Exploitation. However, Child Commercial Sexual Exploitation is still a never ending problem. Therefore, UNICEF as an Organization who on the job for child benefit felt that it is their responsibility to help Nations all around the world fight Child Commercial Sexual Exploitation. Based on this, the formulations of the problem in this research are: What is the position of the child in international law? How is the protection system against Commercial Sexual Exploitation of Children? What are UNICEF’s roles as the international organizations in dealing with the practice of Sexual Exploitation of Children in the world? By using empirical - normative research methods, which combine normative legal approach with several empirical studies, it can be concluded that the children were in accordance with international law are those who are under 18 years old unless, under the law applicable to the child, majority is attained earlier. Children must be protected by the government, local communities and families because they are considered weak and not aware of their rights. Article 34 of the UN Convention on the Rights of the Child states that State parties are obliged to protect the child from all forms of sexual exploitation. UNICEF as an international organization working in the field of children protection felt obliged to assist and cooperate with the countries all around the world to protect children from Commercial Sexual Exploitation of Children and eliminate them. To do so, UNICEF makes an accurate data about Commercial Sexual Exploitation of Children, giving help and rehabilitation for the victim of Commercial Sexual Exploitation of Children, giving the community the right education so they can avoid Commercial Sexual Exploitation of Children, and also helping the government so they by law can handle Commercial Sexual Exploitation of Children that happened in their country. Keyword: Children, Commercial Sexual Exploitation of Children, UNICEF. * Law Student of University of North Sumatra ** Supervisor I *** Supervisor II ABSTRAKSI Maharany Fitri* Dr. Chairul Bariah, S.H., M.Hum.** Arif, S.H., M.Hum.*** Eksploitasi Seksual Komersial Anak (ESKA) merupakan sebuah pelanggaran mendasar terhadap hak-hak anak. Pelanggaran tersebut terdiri dari kekerasan seksual oleh orang dewasa dan pemberian imbalan dalam bentuk uang tunai atau barang terhadap anak, atau orang ketiga, atau orang-orang lainnya. Bentuk-bentuk dari ESKA adalah pelacuran anak, perkawinan anak, pornografi anak, atau pun pariwisata seksual anak. Peraturan hukum internasional pada prinsipnya sudah mengatur mengenai pelarangan ESKA. Akan tetapi, tetap saja ESKA tetap menjadi permasalahan masyarakat dunia yang tak kunjung usai. Maka dari itu UNICEF sebagai Organisasi Internasional yang bergerak demi kepentingan anak merasa sudah menjadi tanggung jawabnya untuk membantu negara-negara di dunia untuk memerangi ESKA. Berdasarkan hal ini, maka rumusan masalah dalam penelitian ini adalah: Bagaimana kedudukan anak dalam hukum internasional? Bagaimana sistem perlindungan anak terhadap Eksploitasi Seksual Komersial Anak? Bagaimanakah peran UNICEF selaku organisasi internasional dalam menangani praktek Eksploitasi Seksual Komersial Anak (ESKA) di dunia? Dengan menggunakan metode penelitian normatif-empiris, yang menggabungkan pendekatan hukum normatif dengan adanya beberapa kajian empiris, dapat disimpulkan bahwa anak yang sesuai dengan hukum internasional adalah mereka yang masih dibawah 18 tahun, kecuali berdasarkan undang-undang nasional berlaku lain. Anak sebagai golongan yang dapat dinilai lemah dan kurang menyadari tentang apa-apa saja haknya, haruslah dilindungi oleh pemerintah, masyarakat sekitar, dan keluarganya. Pasal 34 Konvensi PBB tentang Hak-Hak Anak menyatakan bahwa Pihak negara berkewajiban melindungi anak dari segala bentuk Eksploitasi Seksual. UNICEF sebagai organisasi internasional yang bekerja di bidang perlindungan anak merasa berkewajiban untuk dapat membantu dan bekerjasama dengan negara-negara yang ada di dunia untuk dapat melindungi anak dari Eksploitasi Seksual Komersial Anak (ESKA) dan memberantasnya. Hal tersebut dilakukan UNICEF dengan cara terjun langsung ke lapangan untuk membantu dan membuat data-data yang akurat, memberi bantuan dan rehabilitasi terhadap anak yang telah menjadi korban, memberikan pengajaran terhadap masyarakat agar dapat mengindari ESKA, dan membantu pemerintah untuk secara hukum mampu mengangani kasus ESKA yang terjadi di negara mereka. Kata Kunci: Anak, Eksploitasi Seksual Komersial Anak, UNICEF * Mahasiswa Fakultas Hukum Universitas Sumatera Utara ** Dosen Pembimbing I *** Dosen Pembimbing II